Penggunaan Media Kartu Kuartet untuk Meningkatkan Minat dan Hasil Belajar Peserta Didik pada Pembelajaran Tematik Terpadu di Kelas IV C SDN 71 Kota Bengkulu - Ineke Anidya Prameswari; Sri Dadi; Panut Setiono (JURIDIKDAS, 2022)
This research aims to improve student interest and learning outcomes in integrated thematic learning using quartet card of class IV C students at Elementary School 71 Bengkulu City. The Subjects of this study were teacher and students of class IV C Elementary School 71 Bengkulu City. This research is Classroom Action Research. The data analysis technique used with the observation sheet for measuring learning implementation, test data for measuring learning outcome and questionnaire for knowing student interest. The data analysis technique used with the Observation Sheet uses the formula for the average score, the highest score, the lowest score, the difference in scores and the range of values for each criterion.  The test data was analyzed using the formula of average values and classical learning percentage. The questionnaire was analyzed using the formula of student interest percentage. The average application of quartet card from  cycle I is 69 good categories and in the second cycle is 93,5 very good categories. The average learning interest questionnaires result  of cycle I is 62,97% increase in cycle II which is 88,89%. The result of learning IPS subjects cycle I average was 71,75 with classical completion 55,56% increase in cycle II which is 76,66 with classical completion 85,19%. The result of learning PPKn subjects cycle I, average was 73,33 with classical completion 66,67 %, increase in cycle II  of 80,19 with classical completion 92,60%. Thus, using quartet card as  media can increase student interest and learning outcomes in integrated thematic learning in class IV C Elementary School 71 Bengkulu City.